2023
DOI: 10.1089/neu.2022.0224
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lateral Habenula Dysfunction in Repetitive Mild Traumatic Brain Injury–Induced Motivational Deficits

Abstract: Affective disorders including depression (characterized by reduced motivation, social withdrawal, and anhedonia), anxiety, and irritability are frequently reported as long-term consequences of mild traumatic brain injury (mTBI) in addition to cognitive deficits, suggesting a possible dysregulation within mood/motivational neural circuits. One of the important brain regions that control motivation and mood is the lateral habenula (LHb), whose hyperactivity is associated with depression. Here, we used a repetiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 69 publications
(77 reference statements)
7
20
0
Order By: Relevance
“…Here, we evaluated the effects of mTBI on LHb spontaneous LHb activity (Figure 1A-B, D), LHb neuronal excitability (Figure 2A-B) and intrinsic excitability (Figure 2C-D) in LHb slices from sham and mTBI male and adult mice ~4 weeks post-injury. mTBI increased the overall LHb spontaneous tonic activity while decreasing spontaneous LHb neuronal firing in bursting mode in cell-attached voltage-clamp recordings in male mice as we previously reported 39 , but also resulted in similar changes in female mice (Figure 1B, males: **p<0.01, Figure 1D, females: *p<0.05, Chi squared test). Consistently, LHb neurons of mTBI male and female mice also exhibited significantly higher neuronal excitability in intact synaptic transmission compared to those from sham mice although mTBI-induced LHb hyperexcitability was more pronounced in male mice (Figure 2 A, males: F (1, 836) = 63.46, ****p<0.0001; Figure 2B, females: F (1, 680) = 24.60, ****p<0.0001; sex effect in comparison between mTBI male group from Figure 2A and mTBI female group from Figure 2B: F (1, 806) = 63.69, ****p<0.0001, 2-way ANOVA).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Here, we evaluated the effects of mTBI on LHb spontaneous LHb activity (Figure 1A-B, D), LHb neuronal excitability (Figure 2A-B) and intrinsic excitability (Figure 2C-D) in LHb slices from sham and mTBI male and adult mice ~4 weeks post-injury. mTBI increased the overall LHb spontaneous tonic activity while decreasing spontaneous LHb neuronal firing in bursting mode in cell-attached voltage-clamp recordings in male mice as we previously reported 39 , but also resulted in similar changes in female mice (Figure 1B, males: **p<0.01, Figure 1D, females: *p<0.05, Chi squared test). Consistently, LHb neurons of mTBI male and female mice also exhibited significantly higher neuronal excitability in intact synaptic transmission compared to those from sham mice although mTBI-induced LHb hyperexcitability was more pronounced in male mice (Figure 2 A, males: F (1, 836) = 63.46, ****p<0.0001; Figure 2B, females: F (1, 680) = 24.60, ****p<0.0001; sex effect in comparison between mTBI male group from Figure 2A and mTBI female group from Figure 2B: F (1, 806) = 63.69, ****p<0.0001, 2-way ANOVA).…”
Section: Resultssupporting
confidence: 81%
“…Given the significant lack of preclinical mTBI studies in females as well as studies focused on mTBI-related reward circuit dysfunction in both biological sexes 15,38 , we have developed a preclinical model of mTBI using repetitive closed injury mouse model of mTBI which induces behavioral deficits in motivational self-care grooming in sucrose splash test 39 and social interaction test 40 as well as persistent LHb hyperactivity through a shift in synaptic excitation and inhibition (E/I) balance toward excitation, and via plasma membrane insertion of calcium-permeable (CP) AMPARs in LHb neurons in male mice 39 . We demonstrated that limiting LHb hyperactivity by chemogenetic inhibition of LHb neurons was sufficient to reverse mTBI-induced delays in self-care grooming behavior in male mice supporting a causal link between LHb hyperactivity and mTBI-induced self-grooming deficits 39 . TBI patients also experience neuroendocrine dysfunction [41][42][43][44] with dysregulation of the hypothalamic pituitary axis (HPA) stress neuromodulator, corticotropin releasing factor (CRF), that has significant impact on stress neuronal responses and affective states following mTBI [45][46][47][48][49] .…”
Section: Introductionmentioning
confidence: 99%
“…One of these compounds, J60, was developed by an NIH team who showed it has acceptable behavioral and other effects in mice (Bonaventura et al, 2019), a finding that has been replicated by several other groups (Desloovere et al, 2021; Flerlage et al, 2022; Fleury Curado et al, 2021; Giannotti et al, 2021; Heinsbroek et al, 2021; Huang et al, 2021; Lewis et al, 2020; Li and Hollis, 2021; Salimi-Nezhad et al, 2023; Zhang et al, 2020). J60 efficiently crosses the blood-brain-barrier, it binds directly to central DREADD receptors after i.p.…”
Section: Introductionmentioning
confidence: 94%
“…Maternal deprivation induces LHb hyperactivity through glutamatergic synaptic potentiation that shifts the excitation/inhibition (E/I) balance towards excitation and shows changes in the relative weights of both increased excitatory and decreased inhibitory synaptic inputs onto LHb neurons, and thus produces anxiety-like and depression-like behaviors in adolescent male rats ( 76 ). Another study showed that mild traumatic brain injury diminishes spontaneous glutamatergic and GABAergic synaptic activity onto LHb neurons, while the E/I balance is shifted toward excitation through increased suppression of GABAergic transmission ( 77 ). In the present study, the GABAergic transmission onto LHb neurons were not recorded.…”
Section: Discussionmentioning
confidence: 99%